Neither believer nor infidel : skepticism and faith in Melville's shorter fiction and poetry - Cook, Jonathan A. (Jonathan Alexander), 1953- (Ithaca, New York : Northern Illionois University, Press, Cornell University Press, 2023)
"The first full-length study to explore the relationship between religious doubt and faith in a broad selection of Herman Melville's short stories, novellas, and poetry"-
Neither believer nor infidel: biographical considerations -- Biblical inversion and the ends of Christianity: "Bartleby, the Scrivener" -- Conversion, infatuation, resurrection: Christian salvation in "Cock-a-Doodle-Do!" -- The genealogy of Melville's female Job: Griselda, "Wakefield," Agatha, Hunilla -- Revolutionary skepticism in Israel Potter: the role of Ecclesiastes -- Memorializing the dead in Battle-Pieces: Christian and classical motifs -- "Are ye gods?" Interrogating the divine in Timoleon, etc. -- Legends of the fall: Genesis, Paradise Lost, Schopenhauer, Billy Budd.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on June 16, 2023).
JSTOR
Keywords: Melville, Herman, -- 1819-1891 -- Criticism and interpretation; Melville, Herman, -- 1819-1891; Faith in literature; Skepticism in literature; Foi dans la littérature.; Scepticisme dans la littérature.; LITERARY CRITICISM / Modern / 19th Century .; Faith in literature; Skepticism in literature; Criticism, interpretation, etc; Literary criticism; Critiques littéraires.